2005
DOI: 10.1093/nar/gki460
|View full text |Cite
|
Sign up to set email alerts
|

CEP: a conformational epitope prediction server

Abstract: CEP server () provides a web interface to the conformational epitope prediction algorithm developed in-house. The algorithm, apart from predicting conformational epitopes, also predicts antigenic determinants and sequential epitopes. The epitopes are predicted using 3D structure data of protein antigens, which can be visualized graphically. The algorithm employs structure-based Bioinformatics approach and solvent accessibility of amino acids in an explicit manner. Accuracy of the algorithm was found to be 75% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
189
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(198 citation statements)
references
References 14 publications
0
189
0
2
Order By: Relevance
“…Number of methods that utilize 3D structure of antigens for discontinuous epitope prediction have also been developed. These methods use different approaches for prediction such as solvent accessibility of surface residues [123,124], solvent accessibility with propensity scores [125], and propensity scores with packing density of amino acids [126]. An account of major tools/servers that are involved in conformational epitope prediction is provided in Studies have shown that the analysis of antigen-antibody complex structures is very useful for the characterization of conformational epitopes [134].…”
Section: Computational Prediction Of Allergen Epitopesmentioning
confidence: 99%
“…Number of methods that utilize 3D structure of antigens for discontinuous epitope prediction have also been developed. These methods use different approaches for prediction such as solvent accessibility of surface residues [123,124], solvent accessibility with propensity scores [125], and propensity scores with packing density of amino acids [126]. An account of major tools/servers that are involved in conformational epitope prediction is provided in Studies have shown that the analysis of antigen-antibody complex structures is very useful for the characterization of conformational epitopes [134].…”
Section: Computational Prediction Of Allergen Epitopesmentioning
confidence: 99%
“…However, a few recent studies propose bioinformatics tools based on 3D structure to predict epitopes such as SUPERFICIAL (Goede et al, 2010), Disco tope (Haste Andersen et al, 2006), Conformational Epitope Predictor (CEP) (Kulkarni-Kale et al, 2005), and PEPOP (Moreau et al, 2008). Although, computational methods have different performance; identification and prediction of suitable epitope peptides for vaccine design using these methods are cheaper and quicker than that of experimental screening.…”
Section: Figure 2 Predicted Structures Of B-cell Epitope Peptides Anmentioning
confidence: 99%
“…Although, computational methods have different performance; identification and prediction of suitable epitope peptides for vaccine design using these methods are cheaper and quicker than that of experimental screening. For example, CEP correctly identifies 76% of the amino acid residues known to describe the selected epitopes in data sets consisting of 63 antigen-antibody complexes (Kulkarni-Kale et al, 2005) but Disco Tope detects 15.5% (sensitivity) of residues located in discontinuous epitopes with a specificity of 95%. So, CEP can predict more accurately than Disco tope (Roggen, 2008).…”
Section: Figure 2 Predicted Structures Of B-cell Epitope Peptides Anmentioning
confidence: 99%
“…Some structural prediction programs evaluate similarities in the overall sequences of proteins for specific secondary structures (e.g., likely disulfide bonds, alpha helices, turns) that are likely to dominate secondary shape and may represent an antibody epitope. Others focus on segments of the full-sequence, predicting local structures independent of the overall structure or they predict the overall structure and plot surface exposure [22]. For selected cross-reactive pairs of allergenic proteins, one or more of these structural prediction algorithms is likely to be highly predictive for estimating potential cross-reactivity.…”
Section: Structural Comparisonsmentioning
confidence: 99%